Clinical pattern of vernal keratoconjunctivitis in children – A cross-sectional study - Roopa K; Ramalakshmi Badugu; SreeLakshmi Pallamreddy; Suhasini J (Asian Journal of Medical Sciences, 2024)
Background: Vernal keratoconjunctivitis (VKC), a chronic and bilateral allergic eye condition, predominantly affects young males and is more prevalent in hot, humid regions with high allergen exposure. It manifests with itching, light sensitivity, burning sensations, and tearing. The three main clinical forms include limbal or bulbar, palpebral or tarsal, and mixed presentations. Aims and Objectives: This study aimed to describe the clinical patterns of VKC in children at a tertiary care hospital in Andhra Pradesh. Materials and Methods: This cross-sectional observational study was conducted in a hospital setting at the Department of Ophthalmology, SV Medical College in Tirupati, Andhra Pradesh, between January 2021 and January 2022. Ninety children aged 5–12 years with symptoms of allergic conjunctivitis were enrolled in the study. The Bonini grading system was used to grade the severity of the disease based on clinical manifestations at the time of initial presentation. Results: Mean age of disease onset was 8.6±2.3 years, with a male-to-female ratio (M: F) of 2.1:1. The majority of the subjects experienced seasonal occurrence 69 (77.0%), whereas 21 (23%) had perennial occurrence. The commonly reported symptoms included itching (83%), redness (73%), watering (73%), and discharge (47%). A significant number of patients (60, 69%) had a mixed type of disease that affected both the tarsal and bulbar conjunctiva. Conclusion: VKC predominantly affects young males, displaying a seasonal distribution and showing less allergic association, consistent with patterns observed in other tropical regions. Most patients had mild VKC at presentation, and a mixed-form pattern was most frequently observed.